Dynamics of Chicken Egg Pricing at Simpang Pulai Traditional Market, Jambi City - Riri Gusthia Amanda; Dessy Anggraini (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
This research offers novelty through its specific examination of chicken egg price dynamics in traditional markets from an Islamic economic perspective at Simpang Pulai Market, Jambi City, an area that has received limited scholarly attention. The study aims to analyze the factors influencing price fluctuations and evaluate their conformity with Sharia principles. This research employs a qualitative method with a field research approach through direct interviews with traders and buyers, supported by documentation and literature studies. The findings reveal that price fluctuations are influenced by distributor supply, consumer demand levels, competition among traders, product quality, and consumers’ purchasing power. The pricing mechanism occurs naturally according to market conditions without interventions that disadvantage any party. From the perspective of Islamic economics, these practices reflect the principles of justice, transparency, and mutual consent between sellers and buyers, with no evidence of price manipulation or hoarding practices. The findings highlight that traditional markets function not only as centers of economic transactions but also as spaces capable of creating fair pricing mechanisms aligned with Sharia values, thereby offering a potential model for strengthening Islamic based trading systems.